The Effect of Adding Batak Onion Juice (Allium chinense G. Don) on the Physical and Organoleptic Quality of Chicken Nuggets - Sarina br Nainggolan; Ade Trisna; G A W Siregar (Talenta Publisher, 2024)
Chicken nuggets are processed products that are easily contaminated if the processing and storage of the product are not good. Batak onions contain antioxidant compounds that can prevent oxidative damage to chicken nuggets. This study aims to determine the effect of using Batak onion juice on the physical quality and organoleptic quality of chicken nuggets. The study was conducted at the Technology Research Laboratory, Faculty of Agriculture and the Animal Production Laboratory, Faculty of Agriculture, University of North Sumatra in November 2023. The research design used was RAL (Completely Randomized Design) with 4 treatments, namely P0 = 0%, P1 = 5%, P2 = 10%, P3 = 15% and 5 replications. The parameters of this study were physical quality tests, namely pH, cooking loss, water holding capacity, and organoleptic tests of color, taste, aroma and texture. The results of this study indicate that Batak onion juice with a concentration of 5%, 10%, 15% has a significant effect (P <0.05) on the physical quality and organoleptic quality of taste and aroma in chicken nuggets but does not affect the color and texture